Evaluating the Effectiveness of Poster & Picture Card Media in Teaching the Water Cycle to Elementary Students - Nikmah Fitria Surya; Wenda, Dhian Dwi Nur (Utamax : Journal of Ultimate Research and Trends in Education, 2023)
This study explores the validity, practicality, and effectiveness of Postcard learning media in the classroom. Employing a Research and Development approach, the study utilized the ADDIE model, encompassing Analysis, Design, Development, Implementation, and Evaluation stages. The research was conducted with 17 fifth-grade students at SDN 1 Watudandang. The study involved quantitative analysis to assess the Postcard learning method's implementation, employing a variety of data collection techniques. These included validity questionnaires from media and material experts, teacher and student response questionnaires, and pretest-posttest scores. Validity testing revealed that the Postcard learning media were rated as "very valid" by experts, with scores of 91% from material experts and 84% from media experts. Practicality assessment, based on teacher and student response questionnaires, yielded scores of 91% and 88% respectively, placing it in the "very practical" category. The effectiveness of the media was demonstrated through significant differences in student learning outcomes, as evidenced by pretest and posttest scores. The Paired Samples T Test indicated a t-count greater than the t-table, with a significance value of 0.000. Furthermore, the N-Gain score of 0.75 fell into the "high" category, suggesting that the media were "effective enough". In conclusion, the Postcard learning media proved to be both valid and practical, and sufficiently effective for educational use in teaching fifth graders, notably in enhancing their understanding of the subject matter.